22. EFFECTIVENESS OF NUTRICARE GOLD POWDERED NUTRITIONAL SUPPLEMENT IN PEOPLE REQUIRING RECOVERY AND HEALTH ENHANCEMENT (Vietnam Journal of Community Medicine, 2025)
Objective: To evaluate the effectiveness of Nutricare Gold powdered nutritional supplement in individuals needing recovery and health enhancement in Ninh Binh in 2024.Methods: A randomized controlled intervention study was conducted. Participants were people aged 50 to 70 years selected based on research criteria. The study was implemented and completed in Ninh Binh province in August 2024. The sample size included 120 individuals, with 60 in the intervention group receiving Nutricare Gold powder (50g per serving, twice daily for two months) and 60 in the control group following a regular diet.Results: After two months of intervention, the intervention group showed a decrease in total cholesterol by 0.96 mmol/L, LDL-c by 0.43 mmol/L, and triglycerides by 0.36 mmol/L, while total protein increased by 4.3 g/L and albumin by 3.6 g/L compared to the control group (p
Keywords: Malnutrition; Nutricare Gold; digestion; nutrition; multi-micronutrients